2008
DOI: 10.12968/jowc.2008.17.10.31304
|View full text |Cite
|
Sign up to set email alerts
|

Pressure ulcer predictors in ICU patients: nursing skin assessment versus objective parameters

Abstract: Nursing skin assessment is an important pressure ulcer risk stratification tool in the ICU despite the availability of a large number of objectively measureable ICU specific parameters in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 22 publications
2
90
0
5
Order By: Relevance
“…Current scales for determining the risk for pressure ulcers do not accurately indicate the complexity of the patient's risk, life-saving devices, and comorbid conditions that lead to the development of pressure ulcers. 6,16,17,20,21 Multiple studies of various risk factors for development of pressure ulcers in critically ill patients have been done. In a systematic review, Coleman et al 20 found that no single factor explained the development of the ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Current scales for determining the risk for pressure ulcers do not accurately indicate the complexity of the patient's risk, life-saving devices, and comorbid conditions that lead to the development of pressure ulcers. 6,16,17,20,21 Multiple studies of various risk factors for development of pressure ulcers in critically ill patients have been done. In a systematic review, Coleman et al 20 found that no single factor explained the development of the ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, 16,17 relationships between vasopressor administration and development of pressure ulcers was significant; however, the specific vasopressors used were not identified. In still other studies, the specific vasopressors were indicated, but a generic variable was used for analysis, yielding significant relationships with development of pressure ulcers in both multivariate 18 and univariate 19 analyses. In 2 studies with multivariate analyses, 20,21 norepinephrine was significantly associated with development of pressure ulcers, whereas in another study, 22 moderate doses of norepinephrine were significantly related to development of pressure ulcers.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
“…Duration of mechanical ventilation is also associated with increased risk of pressure ulcer development. [20][21][22] Variables in acuity in ICUs and lack of definitive studies addressing use of mechanical ventilation, vasoactive medi cations, and mobility affect the results in studies of pressure ulcer development. Even if the opinion is that a particular scale overestimates risk, it still identifies that the patient is at risk and encourages the use of preventive measures to prevent pressure ulcers from developing.…”
Section: Pressure Ulcer Risk Assessment Scalesmentioning
confidence: 99%